Acceptable risks of treatments to prevent rheumatoid arthritis among first-degree relatives: demographic and psychological predictors of risk tolerance - Simons, Gwenda; Janssen, Ellen M.; Veldwijk, Jorien; Disantostefano, Rachael L.; Englbrecht, Matthias; Radawski, Christine; Valor-Mendez, Larissa; Humphreys, Jennifer H.; Bruce, Ian N.; Hauber, Brett; Raza, Karim; Falahee, Marie (RMD Open, 2022)
ObjectivesTo quantify tolerance to risks of preventive treatments among first-degree relatives (FDRs) of patients with rheumatoid arthritis (RA).MethodsPreventive treatments for RA are under investigation. In a preference survey, adult FDRs assumed a 60% chance of developing RA within 2 years and made choices between no treatment and hypothetical preventive treatment options with a fixed level of benefit (reduction in chance of developing RA from 60% to 20%) and varying levels of risks. Using a probabilistic threshold technique, each risk was increased or decreased until participants switched their choice. Perceived risk of RA, health literacy, numeracy, Brief Illness Perception Questionnaire and Beliefs about Medicines Questionnaire-General were also assessed. Maximum acceptable risk (MAR) was summarised using descriptive statistics. Associations between MARs and participants' characteristics were assessed using interval regression with effects coding.Results289 FDRs (80 male) responded. The mean MAR for a 40% reduction in chance of developing RA was 29.08% risk of mild side effects, 9.09% risk of serious infection and 0.85% risk of a serious side effect. Participants aged over 60 years were less tolerant of serious infection risk (mean MAR +/- 2.06%) than younger participants. Risk of mild side effects was less acceptable to participants who perceived higher likelihood of developing RA (mean MAR +/- 3.34%) and more acceptable to those believing that if they developed RA it would last for a long time (mean MAR +/- 4.44%).ConclusionsAge, perceived chance of developing RA and perceived duration of RA were associated with tolerance to some risks of preventive RA therapy.
CRIS-Team WoS Importer:2023-01-20